Gestão política das identidades culturais: desafios à democratização - Gonçalves, António Custódio (Africana Studia, 2020)
This article first analyses the main problems induced by some challenges to the new social solidarities and cultural identities related to the so-called "democratic transitions". The text then focuses the critical analysis and constructionist perspective of some political events in Central and Southern Africa.